KINERJA OIL SPILL DISPERSANT DALAM PROSES BIOREMEDIASI TANAH TERCEMAR MINYAK BUMI (STUDI KASUS TANAH TERCEMAR MINYAK BUMI LAPANGAN XYZ) - Imam Chanif, Erliza Hambali, dan Mohamad Yani (Jurnal Teknologi Industri Pertanian, 2017)
Oil spill dispersant (OSD) is a surfactant product that serves as dispersant. OSD has been widely used and proven to be effective in oil spills both in the sea and in the land. The OSD-SBRC (Surfactant and Bioenergy Research Center) IPB was produced from palm oil, while the commercial product of OSD S200 was made from LAS (Linear Alkyl Benzene Sulfonate) based from petroleum. Application of OSD in bioremediation testing occurred on petroleum contaminated soil from the field with initial total petroleum hydrocarbon of 6-10%. The treatment of dispersant to oil ratio (DOR) was at 0.5:1 and 1:1. The contaminated soil was added with Pseudomonas aeruginosa and fertilizers (Urea and SP36) to support bacterial growth. The environmental soil conditions during the bioremediation process were observed as pH, moisture content, and temperature. The OSD performance in bioremediation process was measured as TPH (Total Petroleum Hydrocarbon) and TPC (Total Plate Count).  The results showed that pH, moisture content and temperature levels were at optimum condition for bacterial growth to optimally degrade the hydrocarbon. The result of TPC value showed that treatment with the addition of OSD S200 caused inhibition of microbial growth P. aeruginosa bacteria. The TPH measurements showed that treatment with OSD SBRC with DOR (0.5:1) was able to degrade hydrocarbons up to 89.62%.  The bioremediation process using OSD-SBRC was better than OSD S200.Keywords: bioremediation, hydrocarbon, OSD, surfactant